Peningkatan Hasil Pembelajaran Descriptive Teks Dengan Menggunakan Metode Pembelajaran Kelompok Dalam Pembelajaran Bahasa Inggris Di SMK Bina Profesi Pekanbaru - Muhammad Habibi Akbar; Esti Raihana (Lembaga Pengembangan Kinerja Dosen, 2024)
Learning English at the vocational school level requires the right approach to facilitate students in understanding various types of texts, including descriptive texts. One approach that has been widely used is the group learning method. This study aims to explore the application of group learning methods to descriptive text material in English language learning at SMK Bina Profesi Pekanbaru. The research method used was classroom action research (PTK) which was carried out in several stages. The subjects in this research were 27 class X Accounting students consisting of 22 female students and 5 male students. The data collection technique was carried out by direct observation during the teaching process of Class X Accounting which took place in several meetings. Through conducting observations with English teachers, the implementation of learning can be improved by utilizing discussion and observation methods with students. The results of the research show that the application of the group learning method makes a positive contribution to students' understanding of Descriptive Text material. This research suggests that group learning strategies are good for use in the learning process. This can be seen from the results of the observation sheet before and after the implementation of each stage, namely aspects of student activity, student skills, student enthusiasm and increased student interest. In this case, it also makes students more enthusiastic about carrying out learning activities and makes teachers more creative, conducive learning activities are also achieved by implementing Group Method Learning.